Pembubaran Perseroan Terbatas oleh Kejaksaan Sebagai Upaya Memperkuat Ketahanan Nasional - Andhika Prayoga; Muhammad Sya’roni Rofii (Universitas Medan Area, 2020)
The purpose of this writing is to find out the authority of the prosecutor's office in submitting a request to dissolve a PT in a district court based on the provisions of a Indonesia company law, and its relationship in strengthening national resilience. Furthermore, to examine and analyze this research is by normative legal research by emphasizing discussion on legal-formal (normative) rules and regulations. The data used in this study consisted of primary legal materials including legislation, secondary legal materials such as books and literature and tertiary legal materials obtained through library research. The result of the research is that authority to act as a petitioner for dissolution with the reason if there is a single share ownership (corporate sole) and/or violation of public interest or the law, in the framework of the executive function to uphold the law in society, and that authority is a form of upholding the authority of the government and reflects legal certainty so that it gives effect to the strengthening of national resilience.